Rediscovery of Landraces as a Resource for the Future - Grillo, Oscar (IntechOpen, 2018)
In recent years, all over the world, the attention paid to local and traditional productions is growing, especially in the agro-food sector. Maybe, it is not only due to the impact of globalization and the social and economic changes but also due to the increased consideration to health and nutritional aspects of food. Hence, for economic, social, historical, and nutritional reasons, this trend has led to the rediscovery and reuse of landraces of many different crops, responding to requests for more and more demanding market. This volume collects examples of local crops and old landraces of different areas of the planet that testify the extreme importance of the relation existing among a land, the local productions, the historical traditions, the conservation of biodiversity, the health benefits, the environmental impact and the local economies, also including the significance to dedicate resources to scientific researches in local crops.